Réprimer par le droit : L’intervention de la Brigade nationale de police judicaire dans les procès du Hirak El-Rif - Mariam Benalioua (L’Année du Maghreb)
This article looks at the involvement of the Brigade nationale de police judiciaire (BNPJ) in the judicial management of the Moroccan "Hirak" social movement. This protest movement developed in Morocco's Rif region, following the death of a fishmonger crushed by garbage truck compactor while trying to recover his fish goods confiscated by the authorities. The nascent movement denounced the socio-economic and political marginalization of the region and called for far-reaching reforms for the Rif's development. Accused of "undermining state security", the arrested activists, considered to be the movement's leaders, were sentenced to between 5 and 20 years in prison. Based on interviews with pardoned ex-detainees and lawyers, analysis of court documents, reports by the Equity and Reconciliation Commission (IER), and a press review of all media appearances by BNPJ directors, this article examines how this brigade repressed political dissent. As well as its strategy for fulfilling its principal mission of preserving internal security and maintaining political order, a mission it has been fulfilling since its creation. The political change initiated in Morocco by the consensual alternation of power and the establishment of the Equity and Reconciliation Commission (IER) has forced this brigade to reinvent itself. A look at the historical development of this brigade from the late 1990s to the present day shows how it has broadened its scope of intervention, moving from a brigade dealing only with cases linked to state security, mainly dealing with the files of left-wing political opponents, to a brigade including cases of national scope and falling within the scope of the fight against organized crime (terrorism, drug trafficking, etc.). This rearrangement in its structure and operation has enabled the brigade to professionalize its treatment of political cases, orienting its repressive strategy towards the collection of evidence leading to the criminalization of the protest movement. By describing the arrest and interrogation practices of Hirak activists, this article shows how the BNPJ has abandoned the old methods of enforced disappearance, torture and arbitrary detention, to make the law its weapon of repression. The argument I defend consists in showing how the BNPJ has changed its methods and strategy of repression, from a brigade whose mission was to dismantle clandestine left-wing political organizations through torture and secret detention, with the sole aim of gathering information leading to the location and tracking down of political activists in order to make them disappear, to a Brigade whose strategy of repression involved judicial action, conducting interrogations and drawing up reports aimed at collecting legal evidence that could be used during trials. My presentation is divided into four parts. The first shows how the BNPJ has evolved from a police force specializing solely in state security matters to a brigade with a much broader scope of intervention. The second undertakes to describe how the arrest practices of this brigade correspond to a "confrontational" style of intervention, characterized by the foregrounding of police authority and the use of force ( Maillard and Zagrodzi; 2017). The third part describes the types of practices deployed by this brigade during an interrogation aimed at obtaining a confession. The final section shows how the BNPJ collects incriminating facts in a targeted way, through the creation of PVs, to produce a coherent judicial history.